2019
DOI: 10.1016/j.jor.2019.02.018
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the irrigating solution on articular cartilage in arthroscopic surgery: A systematic review

Abstract: Arthroscopic surgery has become an important and popular orthopedic procedure for numerous joint disorders. Continuous irrigation is performed to replace synovial fluid for optimal joint distension and clear visualization of the synovial cavity. Irrigation solutions may, however, negatively impact articular cartilage and chondrocyte viability. This systematic review aims to compare different irrigating solutions and their properties to determine whether one is superior in its effects on articular cartilage and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 53 publications
0
22
1
Order By: Relevance
“…During arthroscopic surgery, continuous irrigation is performed for the visualization of the knee joint. However, irrigating fluids, such as saline, are known to negatively influence articular cartilage, [3] as they can alter the ideal environment of the knee joint by changing the temperature, osmolarity, and pH of the synovial fluid [4]. Their use during arthroscopic surgery may cause an increased removal of proteoglycans from the knee joint, exposing articular cartilage to possible mechanical damage [5].…”
Section: Introductionmentioning
confidence: 99%
“…During arthroscopic surgery, continuous irrigation is performed for the visualization of the knee joint. However, irrigating fluids, such as saline, are known to negatively influence articular cartilage, [3] as they can alter the ideal environment of the knee joint by changing the temperature, osmolarity, and pH of the synovial fluid [4]. Their use during arthroscopic surgery may cause an increased removal of proteoglycans from the knee joint, exposing articular cartilage to possible mechanical damage [5].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperosmolar synovial fluid (404 mOsm/L; pH 7.7) is diluted and displaced by an isotonic irrigation fluid such as normal saline (308 mOsm/L; pH 5) or lactated Ringer’s solution (273 mOsm/L; pH 6.5). 1,2 Chondrocytes are sensitive to fluctuations in osmolarity, temperature, and pH; this transition may influence the articular cartilage extracellular matrix composition by altering cytoskeletal organization, gene expression, protein synthesis, and calcium signaling. 2-6 Thus, there is strong interest in developing and validating solutions that can maintain and protect the joint, rather than disrupt it.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Chondrocytes are sensitive to fluctuations in osmolarity, temperature, and pH; this transition may influence the articular cartilage extracellular matrix composition by altering cytoskeletal organization, gene expression, protein synthesis, and calcium signaling. 2-6 Thus, there is strong interest in developing and validating solutions that can maintain and protect the joint, rather than disrupt it. 3,7-12…”
Section: Introductionmentioning
confidence: 99%
“…Do not apply a tourniquet During arthroscopy, the synovium and fat pad may need to be partially removed to visualize the anterior part of the menisci. [4,5] However, the bleeding caused by excision of part of the synovium and fat pad results in knee joint effusion, anterior knee pain and affected surgical eld of vision [4] . Therefore, su cient out ow of lavage uid in the knee joint cavity can make the eld of vision clear without stasis in the joint cavity.Drainage is widely used in orthopedic interventions and will, theoretically, remove the initial hemarthrosisSome studies have reported that drains prevent effusions and painful irritation of the knee by reducing synovial irritation, It promotes uid ow out of the joint [5,6] .…”
Section: Introductionmentioning
confidence: 99%